The short- and long-term effects of a computerized reading training program on reading self-concept in second and third grade readers - Ronen Kasperski; Michal Shany; Tal Erez-Hod; Tami Katzir (The Asia-Pacific Society for Computers in Education (APSCE), 2019)
Abstract While computerized reading programs were found to enhance reading skills, less is known about their influence on reading self-concept (RSC). The current study aimed to examine short- and long-term effects of two versions of a computerized reading acceleration program (RAP) on reading skills and reading self-concept. One hundred thirty Hebrew-speaking second to third grade students completed 6 months of training with a computerized reading program. The results revealed significant short-term effects in both conditions for RSC. Furthermore, at the posttest, RSC of struggling readers was significantly higher in comparison to the RSC of second to third grade struggling readers from an age-matched normative sample that did not receive the reading training. Importantly, these gains remained evident 6 months after training was completed.